THE FINAL PERIOD OF THE TURKIC KHAGANATES IN ENGLISH-LANGUAGE SCHOLARSHIP - Yuldashaliyeva Oyistakhon Orifjon qizi (Bright Mind Publishing, 2025)
This article explores the final phase in the history of the Turkic Khaganates based on English-language scholarly research, focusing on the political, military, and diplomatic developments of the mid-8th century and beyond. The study addresses the fragmentation of the Eastern and Western Turkic Khaganates, dynastic struggles, and the complex interactions between nomadic and sedentary powers, as well as their relations with the Tang Empire, the Umayyad Caliphate, and Tibet. English-language sources portray this era not merely as a period of decline, but as one of political transition and the emergence of new powers. This analytical approach contributes to a broader understanding of the historical legacy of Turkic peoples and the place of Central Asia in global history.
Keywords: Turkic Khaganate, Tang Empire, 8th century, Tang-Turk relations, Umayyads, geopolitics, nomads, English-language research.